2006
DOI: 10.1111/j.1439-0523.2006.01253.x
|View full text |Cite
|
Sign up to set email alerts
|

The transfer of a gene conferring resistance to scald (Rhynchosporium secalis) from Hordeum bulbosum into H. vulgare chromosome 4HS

Abstract: The transfer of a gene conferring resistance to scald (Rhynchosporium secalis) from Hordeum bulbosum into H. vulgare chromosome 4HS R. Pick er ing 1 , B . R ug e-We hl i ng 2 , P . A . J oh ns t on 1 , G. Schwe izer 3 , P. Ack erm an n Abstract Scald is a serious foliar disease that infects barley (Hordeum vulgare L.) causing reduced yields and adversely affecting quality. A means to combat the disease is to breed cultivars that possess genetic resistance. However, all known resistance alleles have so far orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 16 publications
2
35
0
3
Order By: Relevance
“…Some resistance genes originate from wild barley, for example from H. vulgare subsp. spontaneum Rrs12 on 7HS, Rrs13 on 6HS, Rrs14 on 1HS, and Rrs15 on 7HL (Abbott et al 1992;Abbott et al 1995;Garvin et al 1997;Garvin et al 2000;Genger et al 2003a;Genger et al 2003b;Genger et al 2005), or from Hordeum bulbosum Rrs16 on 4HS (Pickering et al 2006). Furthermore, a number of QTL studies revealed QTLs for scald resistance on several chromosomes whose loci often coincided with locations of known scald resistance genes (Backes et al 1995;Bjørnstad et al 2004;Cheong et al 2006;Genger et al 2003;Grønnerød et al 2002;Spaner et al 1998;Thomas et al 1995;von Korff et al 2005;Wagner et al 2008;Yun et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Some resistance genes originate from wild barley, for example from H. vulgare subsp. spontaneum Rrs12 on 7HS, Rrs13 on 6HS, Rrs14 on 1HS, and Rrs15 on 7HL (Abbott et al 1992;Abbott et al 1995;Garvin et al 1997;Garvin et al 2000;Genger et al 2003a;Genger et al 2003b;Genger et al 2005), or from Hordeum bulbosum Rrs16 on 4HS (Pickering et al 2006). Furthermore, a number of QTL studies revealed QTLs for scald resistance on several chromosomes whose loci often coincided with locations of known scald resistance genes (Backes et al 1995;Bjørnstad et al 2004;Cheong et al 2006;Genger et al 2003;Grønnerød et al 2002;Spaner et al 1998;Thomas et al 1995;von Korff et al 2005;Wagner et al 2008;Yun et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In total, 43QTLs and seven genes conferring quantitative and qualitative resistance to R. secalis have been located on individual maps (Abbott et al 1992(Abbott et al , 1995Backes et al 1995;Bjornstad et al , 2004Cheong et al 2006;Garvin et al 1997Garvin et al , 2000Genger et al 2003aGenger et al , b, 2005Gronnerod et al 2002;Jensen et al 2002;Li and Zhou 2011;Patil et al 2003;Pickering et al 2006;Sayed et al 2004;Schweizer et al 1995Schweizer et al , 2004Shtaya et al 2006;Spaner et al 1998;von Korff et al 2005;Wagner et al 2008;Yun et al 2005). Here, we integrated all these QTLs and genes into a consensus map to assess the genetic variation of scald resistance (Fig.…”
Section: Diversity Of Qtls and Genes For Rhynchosporium Resistance Inmentioning
confidence: 99%
“…Rrs1 is a complex locus on the long arm of chromosome 3H with multiple alleles (Graner and Tekauz 1996;Bjornstad et al 2002Bjornstad et al , 2004. Other genes include Rrs13 on chromosome 6H (Abbott et al 1995;Genger et al 2003b), Rrs2, Rrs12 and Rrs15 on chromosome 7H (Abbott et al 1992;Genger et al 2003aGenger et al , b, 2005Schweizer et al 1995), Rrs14 on chromosome 1HS (Garvin et al 1997(Garvin et al , 2000 and Rrs16 on chromosome 4HS (Pickering et al 2006). In addition, a number of QTLs for scald resistance have been identified on all chromosomes except chromosome 5H (Backes et al 1995;Li and Zhou 2011;Sayed et al 2004;Spaner et al 1998;Yun et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Plants were sprayed uniformly with inoculum and left for 20 minutes to dry. Inoculated plants were then lightly sprayed with water and kept for 48Á 72 hours in a dark moist chamber at 188C and then transferred onto glasshouse benches at 16Á188C (Pickering et al 2006). Samples were collected one week and two weeks after infection.…”
Section: Infection Experiments With Rhynchosporium Secalis and Gaeumamentioning
confidence: 99%